Prospects of Liposomes Application in Agriculture - Kyrychenko, A.M.; Kovalenko, O.H.; Кириченко, А.М.; Коваленко, О.Г. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
Liposomes are artificially or spontaneously formed hollow structures whose contents are limited to a single, double, or multiple lipid membrane. Liposomes can be formed by amphiphilic substances encapsulating an aqueous solution of any substance under certain conditions. Liposomes have been very successfully used in the pharmaceutical, cosmetic, and food industries, but there is only limited information on the application of this technology in agriculture. Therefore, the purpose of the review is to summarize the information available since liposome discovery in the 1960s to date on the main properties of liposomes and their production technologies as well as analyze published data on the use of these supramolecular structures in agriculture, mainly as a means of storing, absorbing, and delivering pesticides or antiviral substances to plants.